Biotechnology to improve resistance to pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Scientists at IRRI (International Rice Research Institute) are using biotechnology to transfer the natural pest resistance found in wild rices into domesticated varieties, and thus develop improved cultivars that require few or no pesticides. Up...